Communicating Corporate Social Responsibility in the post mandate period: Evidence from India - Nayan Mitra; Asif Akhtar; Ananda Das Gupta (International Journal of Corporate Social Responsibility (JCSR), 2018)
The concept of Corporate Social Responsibility (CSR) underwent a overhaul in India for certain large, stable companies post the passing of the Companies Act, 2013. It transited from being a voluntary, sporadic exercise to mandated, objective, structured, transparent and accountable compliance - not only to the Government, but also to the other stakeholders and most importantly, to the Companies themselves. As a result, Corporate Communication on CSR became extremely relevant. Moreover, study of mandated CSR (here, under the Section 135 and Schedule VII of the Companies Act, 2013) also became a new area for knowledge creation.Although, much research has been done in the past to assess the relationship of CSR Communication with CSR and study the relationship of CSR with regards to Firm Performance, yet, this investigation remains the first empirical study done in the post-mandate period between the years 2015-2017, barely two years since the Act came into existence.
Keywords: 650; Corporate social responsibility; CSR communication; CSR mediator; Emerging economies; Empirical study; Firm performance; Image; India; India CSR; Intangible benefits; Mandated CSR; Reputation; Schedule VII; Section 135